2015
DOI: 10.1111/plb.12311
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal variation of nectar robbing in Salvia gesneriflora and its effects on nectar production and legitimate visitors

Abstract: Nectar robbing occurs when floral visitors remove floral nectar through floral damage and usually without providing pollination in return. Even though nectar robbing may have negative, neutral or even positive effects on plant fitness, few studies have investigated temporal and spatial variation in robbing rate and their consequences, particularly in the tropics. In this study, robbing levels were estimated during 3 years in four populations of Salvia gesneriflora, a hummingbird-pollinated shrub endemic to cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
(71 reference statements)
2
18
0
1
Order By: Relevance
“…Similar to previous studies revealing great variation in nectar robbing among individuals, species, sites, seasons, and years (Morris, 1996;Olesen, 1996;Navarro, 2000;Arizmendi, 2001;Irwin et al, 2001;Utelli & Roy, 2001;Irwin & Maloof, 2002;Cuevas & Rosas-Guerrero, 2016;Rojas-Nossa et al, 2016), we also established that nectar robbing of S. przewalskii varied spatiotemporally. In addition, our survey indicated that in all of the communities, only S. przewalskii was a target of nectar robbing.…”
Section: Population-level Nectar Robbing Varies Across Sites and Yearssupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to previous studies revealing great variation in nectar robbing among individuals, species, sites, seasons, and years (Morris, 1996;Olesen, 1996;Navarro, 2000;Arizmendi, 2001;Irwin et al, 2001;Utelli & Roy, 2001;Irwin & Maloof, 2002;Cuevas & Rosas-Guerrero, 2016;Rojas-Nossa et al, 2016), we also established that nectar robbing of S. przewalskii varied spatiotemporally. In addition, our survey indicated that in all of the communities, only S. przewalskii was a target of nectar robbing.…”
Section: Population-level Nectar Robbing Varies Across Sites and Yearssupporting
confidence: 89%
“…It has been proposed that spatiotemporal variations in nectar robbing can be explained by two variables: the local availability of alternative floral resources and the abundance of floral visitors (Navarro, 2000;Irwin et al, 2001;Irwin & Maloof, 2002;Cuevas & Rosas-Guerrero, 2016;Rojas-Nossa et al, 2016); however, direct experimental evidence is still needed to support these explanations. Our results confirmed these arguments and provided evidence to explore these relationships in detail.…”
Section: Nectar Robbing Is Influenced By the Floral Diversity As Wellmentioning
confidence: 99%
See 2 more Smart Citations
“…Se han logrado avances sustanciales en el entendimiento de sus relaciones filogenéticas (Walker et al 2004, Walker & Sytsma 2007, Drew et al 2017, Fragoso-Martínez et al 2017a. En adición, se han realizado algunos estudios cromosómicos (Epling et al 1962, Palomino et al 1986, Mercado et al 1989, anatómicos (Ceja-Romero et al 2005, Castro-Morales 2008, genéticos (Cahill 2004), quí-micos (Wasson 1962, Sánchez et al 1989, Argumedo et al 2003 (Dieringer et al 1991, Claßen-Bockhoff et al 2004, Wester & Claßen-Bockhoff 2006, Arizmendi et al 2007, Benitez-Vieyra et al 2014, Cuevas & Rosas-Guerrero 2016.…”
Section: Martha Martínez-gordillo Et Alunclassified